2019
DOI: 10.3390/met9020139
|View full text |Cite
|
Sign up to set email alerts
|

Wear Behavior of CuSn Coated Piston Ring Sliding against Nodular Cast Iron Cylinder Liner under Heavy-Duty Conditions

Abstract: In order to investigate the friction and wear behavior between the nodular cast iron cylinder liner (Fe) and CuSn coated piston ring under heavy-duty conditions, piston rings with chromium(Cr) coating and CuSn-Cr coating were tested using the piston ring reciprocating liner test rig at the simulated working conditions of 56 MPa, 200 r/min, 190 • C. Compared with the Cr/Fe pair, the CuSn coating consumption of the CuSn-Cr/Fe pair made friction coefficient and cylinder wear loss decrease by 2.8% and 51.5%, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Furthermore, the study emphasized the influence of the W content on the mechanical properties of the Ni-W alloy coating, revealing that a higher W content led to finer grain refinement and increased coating hardness. In another study by Li et al [25], a Cu-Sn coating was deposited on a Cr-coated piston ring sample. Through friction testing between the piston ring sample and a nodular cast iron cylinder liner sample, it was observed that the Cu-Sn/Cr coating reduced the friction coefficient by 2.6% and cylinder liner wear by 51.8%.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the study emphasized the influence of the W content on the mechanical properties of the Ni-W alloy coating, revealing that a higher W content led to finer grain refinement and increased coating hardness. In another study by Li et al [25], a Cu-Sn coating was deposited on a Cr-coated piston ring sample. Through friction testing between the piston ring sample and a nodular cast iron cylinder liner sample, it was observed that the Cu-Sn/Cr coating reduced the friction coefficient by 2.6% and cylinder liner wear by 51.8%.…”
Section: Introductionmentioning
confidence: 99%
“…One or more materials of the running-in coating can be designed according to the running-in conditions, which has a significant effect on reducing gas channeling, fuel consumption and emission. Li et al 13 deposited Cu-Sn coating on Cr plated piston ring sample. The friction test between piston ring sample and nodular cast iron cylinder liner sample showed that through using the Cu-Sn/Cr coating, the friction coefficient and cylinder liner wear were reduced by 2.6% and 51.8% respectively.…”
Section: Electroplating Coating On Piston Ringmentioning
confidence: 99%
“…The maximum combustion gas pressure and the temperature are usually achieved when the piston is nearly at the top dead center (TDC) of the cylinder liner [18][19][20][21], where the sliding speed between PRCL is close to zero and almost no lubricating oil film can be formed. When the piston is approaching and departing the TDC, the sliding speed is low as well, usually causing the mixed lubrication even the boundary lubrication.…”
Section: Tribo-testers and Test Detailmentioning
confidence: 99%